PENGARUH KONSENTRASI GELATIN DAN SUKROSA TERHADAP KUALITAS FISIK, KIMIA DAN SENSORIS PERMEN JELLY TOMAT (Lycopersicum esculentum Mill) - Grace, Pangalila A.; Nurali, Erny J. N.; Assa, Jan R. (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2021)
The candy circulating in the community consists of two types, namely hard candy and soft candy. Jelly candy includes soft candy that is liked by many people from children to young people because of its different texture compared to other candies. The raw material used in this study is tomatoes because tomatoes are abundant in Indonesia but tomatoes do not have long shelf life. This study aims to determine the effect of gelatin and sucrose concentrations on the physical, chemical and sensory quality of tomato jelly candy (lycopersicum esculentum). This study used a factorial completely randomized design consisting of 2 factors, namely the concentration of gelatin and sucrose. The results showed that the concentration of gelatin 25% and sucrose 50% affected the sensory properties of making jelly tomato candy which included aroma with yield 2.89%, color 3.35%, taste 3.72%, texture 3.45%, while for sucrose content of 25.53% with a elasticity of 8.5 mm/g/s